2010
DOI: 10.1111/j.1600-048x.2009.04735.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing parentage in parasitic birds: an evaluation of methods to detect conspecific brood parasitism using goldeneyesBucephala islandicaandBl. clangulaas a test case

Abstract: Conspecific brood parasitism (CBP) occurs in over 200 species of birds. Efforts to detect CBP have relied on either observational criteria, or more recently, on molecular methods. While molecular approaches are powerful, they are expensive, time consuming and may prove prohibitive for studies requiring estimates of CBP over large spatial and temporal scales involving hundreds of nests. We evaluated a series of observational methods that have been applied in previous studies to detect CBP, using two species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 62 publications
0
29
1
Order By: Relevance
“…In the absence of genetic analyses of the putatively parasitic eggs laid in our study, alternative explanations for the patterns of egg laying detected in our experimental treatment, which do not invoke parasitism by the focal females, cannot be entirely ruled out (Latif et al 2006;Eadie et al 2010). However, given the apparent absence of Trials where there was evidence of parasitism in the group following the manipulation are marked Y; trials in which there was no evidence of parasitism are marked N d Females in these pairs did not lay eggs the day following the manipulation, but after this single-day delay, a parasitic egg did appear in the aviary e The female in this pair was seen attempting to enter a neighbouring nest and being chased away by the nest-occupiers the morning following the manipulation, before laying her egg from the perch any putative evidence of brood parasitism in control trials (as indicated by the lack of supernumerary eggs in any of the active nests or the presence of new eggs in the simulated nests), it remains reasonable to infer that parasitism took place following the removal of a female's nest when eggs appeared in simulated active nests, or when more than one egg was laid in a real active nest in the 24 h following the experimental manipulation.…”
Section: Discussionmentioning
confidence: 76%
“…In the absence of genetic analyses of the putatively parasitic eggs laid in our study, alternative explanations for the patterns of egg laying detected in our experimental treatment, which do not invoke parasitism by the focal females, cannot be entirely ruled out (Latif et al 2006;Eadie et al 2010). However, given the apparent absence of Trials where there was evidence of parasitism in the group following the manipulation are marked Y; trials in which there was no evidence of parasitism are marked N d Females in these pairs did not lay eggs the day following the manipulation, but after this single-day delay, a parasitic egg did appear in the aviary e The female in this pair was seen attempting to enter a neighbouring nest and being chased away by the nest-occupiers the morning following the manipulation, before laying her egg from the perch any putative evidence of brood parasitism in control trials (as indicated by the lack of supernumerary eggs in any of the active nests or the presence of new eggs in the simulated nests), it remains reasonable to infer that parasitism took place following the removal of a female's nest when eggs appeared in simulated active nests, or when more than one egg was laid in a real active nest in the 24 h following the experimental manipulation.…”
Section: Discussionmentioning
confidence: 76%
“…Before molecular‐genetic methods became available, CBP was often inferred by larger than normal clutch size, addition of more than one egg per day, addition after incubation start, and differences in egg size, shape and colour (reviewed by Eadie & Savard, ). Such methods have limited detection power: in goldeneyes, three of these criteria together identified 75% of parasitized nests (Eadie et al ., ). Combination of more than one egg added per day, or a clutch exceeding 12 eggs, in goldeneyes detected less than half of the parasitic eggs found by protein fingerprinting (Andersson & Åhlund, ).…”
Section: Methodsmentioning
confidence: 99%
“…The large frequency of conspecific mixed broods is also consistent with the observation that there is a significant relationship between mixed broods and brood size, since adoption and parasitism directly contribute to brood size. In avian studies, this same relationship between clutch size and parasitism has been observed and has been used as a method for detecting brood parasitism (Eadie, Smith, Zadworny, Kühnlein, & Cheng, ).…”
Section: Discussionmentioning
confidence: 63%